Neuropsychological Correlates of Suicidal behavior - Hodgkinson, S.; Jandl, M.; Kaschka, W. P. (Nervenheilkunde, 2017)
Cognitive theories of suicidal behavior postulate that the behavior of a suicidal individual stems from their irrational thoughts about negative and unpleasant events. Cognitive neuropsychology aims to understand how these (aberrant) cognitive processes relate to areas of the brain responsible for memory, speech, pattern recognition and problemsolving. Several neuropsychological correlates of suicidal behavior have been identified and a battery of neuropsychological tests have been used to compare individuals exhibiting suicidal behavior with those that do not. Drawing on the available research literature, we ask whether suicidal behavior has a distinct neuropsychological ‘signature’ and if so, what this signature tells us about its aetiology.
Keywords: Suicidal behavior; neuropsychological tests; cognitive rigidity; memory deficits; decisionmaking deficits; irrational behavior